2021
DOI: 10.3390/su132212524
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Cheese with Focus on Food Safety—A Segmentation Analysis

Abstract: This research work analyzes Albanian urban consumer preferences and purchasing behavior related to cheese, focusing on food safety and related attributes, including origin, packaging, and certification. This paper is based on a structured survey targeting urban consumers. The analysis consists of a two-step cluster and descriptive statistics. The clustering was based on key sociodemographic variables, namely, gender, education, and age. The results show that the local cheese is preferred to imported cheese, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our results indicate that the purchase selection of cheese by the consumers has not changed through the pandemic, since the cross-shopping behavior of consumers for food studied for more than a decade or so [43] provides the supermarket as the first choice, even reaching 76.4% for cheese [44], comparable with our finding of 90% after the pandemic. Another study within the pandemic in Albania also proved the first selection choice of the supermarket for traditional local cheese purchase among educated male and female participants, with lower percentages, however, around 40% [27]. Laguna et al report a reduction in shopping frequency but no changes in shopping location during the pandemic [45].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that the purchase selection of cheese by the consumers has not changed through the pandemic, since the cross-shopping behavior of consumers for food studied for more than a decade or so [43] provides the supermarket as the first choice, even reaching 76.4% for cheese [44], comparable with our finding of 90% after the pandemic. Another study within the pandemic in Albania also proved the first selection choice of the supermarket for traditional local cheese purchase among educated male and female participants, with lower percentages, however, around 40% [27]. Laguna et al report a reduction in shopping frequency but no changes in shopping location during the pandemic [45].…”
Section: Discussionmentioning
confidence: 92%
“…Most hot pepper cheese consumers preferred their cheese with higher heat intensity and were also motivated by the visual characteristics of it [26]. A segmentation analysis conducted by Zhllima et al revealed that local cheese is preferred to imported cheese, and the main selection criteria for food are the producer name/brand and knowing the seller, with educated female consumers buying cheese mainly in supermarkets [27]. Attitudes for sustainable mountain cheese show the influence of green consumers' values on the brand choice and the strong relationship between the values of green consumers and animal well-being [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The clustering solution is considered poor when the silhouette measure is < 0.20, values of > 0.50 indicate a good and intermediate values an acceptable clustering solution (Mooi and Sarstedt 2011). Two-step cluster analysis is considered to be more accurate and reliable compared to other clustering methods and was extensively used in different fields (Tkaczynski 2016) and in numerous consumer studies (Geeroms et al 2008;Miloradovic et al 2021;Zakowska-Biemans 2011;Zhllima et al 2021).…”
Section: Discussionmentioning
confidence: 99%